(untitled) (Revista Argentina de Cirugía, 2026)
Hepatocellular adenoma (HCA) uptake of 18FDG uptake on PET-CT is rare. This situation poses doubts about the differential diagnoses and treatment. The aim of this article is to perform a mini review of 18FDG avid HCA over the past 37 years and to describe a new case presentation. Based on a study conducted by other authors between 1984 and 2014, we extended the search until 2021 using the same keywords. The relevant data were analyzed. Between 1984 and 2021 we detected 38 cases in 37 years. HCAs were more common in women of childbearing age. The most common types were H-HCA an I-HCA. Surgical resection was the treatment most used. Cell differentiation and glucose and lipid metabolic diseases would favor 18FDG uptake. Liver resection provides better outcomes, allowing for a complete examination of the lesion.